A FORMALIST-STRUCTURALIST ANALYSIS OF THE NOVEL SAB‘ATU AYYĀM FAQATH BY WAIL WAJDI - Puspita, Neng Nadila; Akbar, Doni Wahidul (Universitas Islam Negeri Sumatera Utara Medan, 2026)
Literature is defined as a creative work of humankind that utilizes language in its creation. There are many forms of literary works, including novels. As a medium of expression, novels allow authors to systematically convey ideas, experiences, and social reflections, enabling readers to interpret the meaning and values contained within. This research aims to examine intrinsic elements and show the relationship between structural elements in the novel. Sab ‘atu Ayyam Faqath karya Wail Wajdi ini. This research is included in the qualitative research type. Descriptive. The technique used in this research is structural formalism, which views literary works as a complete and whole structure where intrinsic relationships are generated.Data analysis techniques include the disclosure method (identification and description) and the systematic analysis method (examining the relationship between elements).ResultsThis research shows that the novel's structure is very cohesive. The story elements center on the father's physical and psychological suffering, driving the main plot. The central character, Wail Wajdi, emphasizes strong motifs of devotion and loyalty. This research answers the intrinsic elements contained in the novel and reveals the coherence or relationship between the elements. This research can also providetheoretical contribution to the study of Arabic literature and serve as a reference in improving the ability to understand Arabic texts.